2008
DOI: 10.1159/000121420
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 Antichymotrypsin Gene Signal Peptide A/T Polymorphism and Primary Intracerebral Hemorrhage

Abstract: Background/Aims: Alpha-1 antichymotrypsin (ACT), a serine proteinase inhibitor, has been implicated in vascular pathology. The TT genotype of the ACT signal peptide A/T polymorphism has been reported to confer susceptibility to primary intracerebral hemorrhage (PICH). We conducted a prospective study to test possible association of ACT signal peptide A/T polymorphism with PICH in a Greek cohort with enough power (80%) to detect a twofold increase in the odds ratio. Methods: We prospectively recruited 147 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 77 publications
3
7
2
1
Order By: Relevance
“…In a Chinese study, a significant gene-environment interaction, referred to as a super multiplicative type 4 interaction, was shown between both ACT AT and TT genotypes and primary hypertension, which is not fully consistent with other results [109] . On the other hand, some results support the data, suggesting a lack of association between the ACT A/T polymorphism and PICH [110] .…”
Section: Alpha-1 Antichymotrypsin (Act)supporting
confidence: 56%
“…In a Chinese study, a significant gene-environment interaction, referred to as a super multiplicative type 4 interaction, was shown between both ACT AT and TT genotypes and primary hypertension, which is not fully consistent with other results [109] . On the other hand, some results support the data, suggesting a lack of association between the ACT A/T polymorphism and PICH [110] .…”
Section: Alpha-1 Antichymotrypsin (Act)supporting
confidence: 56%
“…54 However, these associations were not replicated in a study from Poland 55 and in a group of 147 Greek patients from our department. 56 In our group we observed only a marginal association in the non-hypertensive group (p=0.05). It is possible that in nonhypertensive patients the absence of hypertension unmasks the relatively minor effects of ACT A/T signal peptide polymorphism on the cerebral vasculature, making it more susceptible to haemorrhage.…”
Section: Alpha-1 Antichymotrypsin Genecontrasting
confidence: 57%
“…Fu et al reported increased risk of ICH in a Chinese population carrying with ACT-AT or TT genotypes [ 16 ]. However, these findings failed to be replicated by other studies [ 17 20 ]. The inconsistency might be attributed to the small sample size and the subsequent insufficient statistical power, different ethnic background, or even the potential existence of selection bias.…”
Section: Introductioncontrasting
confidence: 58%